Peningkatan Kesadaran Masyarakat Urban terhadap Transportasi Berbasis Sepeda - Chandra Lukita; Mamih Maya Pebiyanti; Henry Henry; Hana Maria Tan; Dadi Adriana; Aswadi Jaya (ADI Pengabdian Kepada Masyarakat, 2025)
Urban environmental issues, such as increasing air pollution and the reduction of green spaces, have become serious challenges due to the high usage of motor vehicles that produce carbon emissions. This air pollution has a detrimental impact on public health and quality of life. As an alternative, bicycles as environmentally friendly means of transportation are considered capable of reducing pollution and supporting urban greening programs. Bicycle use also has the potential to reduce traffic congestion and improve air quality. This community service aims to analyze the benefits of bicycle usage in mitigating the negative impacts of conventional transportation on the environment and to identify the obstacles in its implementation. The methods used include surveys of urban communities regarding their transportation patterns, observations of supporting infrastructure for bicycles, and analysis of existing sustainable transportation policies in the city. The results of the community service show that increasing bicycle usage can lower carbon emissions, reduce congestion, and improve air quality. Additionally, reducing land usage for roads and motor vehicle parking opens opportunities for expanding green spaces in the city, which in turn can improve the quality of life for the community. However, there are obstacles such as the lack of safe bicycle lanes, insufficient supporting facilities, and low public awareness of the benefits of cycling. Therefore, more comprehensive policies, development of cyclist-friendly infrastructure, and educational campaigns are needed to increase community participation.